The Quantitative Model of the Business Success Based on Entrepreneurial Characteristics, Motivation And Business Ability - Riyanto, Agus; Maula, Ismatul; Syafei, M. Yani; Sianturi, Gabriel; Fadhilla, M Azka (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyse the influence of entrepreneurial characteristics, motivation and business capabilities on business success in printing companies. The method used in this research is descriptive and verification with a sample of 63 respondents. The analysis used in this research is multiple linear regression analysis and coefficient of determination analysis with hypothesis testing using the T test and F test using SPSS V22 software. The results obtained by multiple linear regression analysis are as follows: Simultaneously entrepreneurial characteristics, motivation and business capabilities have a significant effect on business success in printing companies.